PENDIDIKAN DALAM DUNIA SUFISTIK - Khoirurrijal Khoirurrijal (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
Moral deviation that occurs in most people because they growt in a poor educational environment. So how urgency of an education that is able to bring the hope of the nation's generation to the peak height of morals spread happiness and tranquility. Sufi or moral importance of education requires an educator in order to keep their students from evil and ugliness. With Sufi education students probably will not do anything bad. Three principal Sufi teachings in the world of education are reflected in akhlâqi sufism, amali sufism and philosophical sufism. Akhlâqi sufism aimed at cleansing the soul of passion that is not good towards the divine presence. Amali sufism aims to fill one's heart after cleaning of the properties despicable how to understand and practice the commendable traits through inner and outer aspects. Philosophical sufism can not be regarded as a philosophy, because the teachings and methods based on taste (dzauq).